Towards the violated face: the Mugshot of Bophana and the Cambodian tragedy - Lessa Filho, Ricardo; Vieira, Frederico (MATRIZes, 2022)
Can a face in fact be totally annihilated? From this provocation, we aimed at the mugshot of Bophana, the guiding thread of this text. The essay tries to reflect on the vestigial testimony of her face based on philosophical concepts present in Lévinas and Butler, seeking a policy of images, especially those that expose faces and bodies victimized by violence. We also sought to understand the method of filmmaker Rithy Panh, who made an important documentary on the memory of the Cambodian genocide motivated by Bophana’s photograph. By making the archival images of the extermination a kind of gravestone for the dead, Panh’s method also approaches the epistolary gesture present in the elimination of Bophana and her husband, Ly Sitha.